Non-pylori Helicobacters (NHPHs) Induce Shifts in Gastric Microbiota in Helicobacter pylori-Infected Patients - Peng, Xianhui; Zhou, Liya; Gong, Yanan; Song, Zhiqiang; He, Lihua; Lin, Sanren; Zhang, Jianzhong (Frontiers in Microbiology, 2017)
In addition to Helicobacter pylori, other members of the genus Helicobacter, i.e., gastric non-pylori Helicobacter (NHPH) species, are also associated with a range of gastric diseases. The dysbiosis of the gastric microbiota plays an important role in the development of gastric disease. However, due to the relatively low prevalence of NHPH species and the fastidious nature of these organisms, the effects of NHPH species on the structure and function of gastric microbiota are difficult to assess. Progress in sequencing technology makes this research possible. In this study, we investigated the effects of NHPH species (H. suis, H. felis or H. salomonis) and H. pylori coinfection on the stomach microbial composition of gastric mucosa specimens from patients with gastric disorders by applying 16S rRNA gene deep sequencing. The species-specific influence of NHPHs on the structure of the gastric microbiota was indirectly characterized by comparing variations between H. pylori mono- and coinfection samples. In addition, we predicted gene functions and metabolic pathways associated with variations in the gastric bacterial community between the H. pylori mono- and coinfection groups. We found marked structural and functional variations in the gastric microbiota between H. pylori mono- and coinfection samples. Compared with the H. pylori monoinfection (H. pylori only) group, both the HPHS and HPHF (H. pylori/H. suis and H. pylori/H. felis coinfections, respectively) groups showed significant increases in phylotype richness and significant decreases in β diversity, but the HPHM (H. pylori/H. salomonis coinfection) group did not. Regarding the top five phyla and top thirty-five genera, the HPHS and HPHF groups had similar variation trends in relative abundance. The increased relative abundance levels of the genera Vibrio, Pseudoalteromonas, Photobacterium and Clostridium may be associated with increases in predicted signal transduction/metabolic pathways among the three coinfection groups. The relative abundance levels of bacteria involved in the formation of N-nitroso compounds were significantly decreased in the HPHS and HPHF groups, including the genera Streptococcus, Prevotella, Escherichia, Neisseria, Pseudomonas, Haemophilus, Campylobacter, Veillonella, Lactobacillus, Clostridium and Bacteroides. The significantly decreased relative abundance levels of the phyla Firmicutes and Bacteroidetes in the HPHS and HPHF groups may be associated with the